Upper cretaceous staphylinidae from Orapa Diamond Mine in Botswana - Mnguni, Sandiso (My University, 2022)
A fauna of Mid-Cretaceous Staphylinidae (Coleoptera) recovered from a Turonian crater-lake in Orapa Diamond Mine in Botswana is described. These are assigned to the following subfamilies: Steninae, Tachyporinae and Paederinae, respectively. Three new species have been erected; these are: Afristenus orapensis species nov., Cretatachinus orapensis species nov., and Afrinophilina orapa species nov., respectively. Furthermore, the paederine, Afrinophilina orapa, is the earliest occurrence of a member of the Pinophilina, and the stanine, Afristenus orapensis, is a new genus for the family. These are, with the exception of one species from Santana/Crato Formation, a Lower Cretaceous deposit in Brazil, the first Cretaceous fossil staphylinids from the southern hemisphere. The location, geology and geography, and history of the deposit are provided. The dating of the kimberlites, sediments, and rate of sedimentation are also briefly discussed. Previous publications from the deposit, and the associated palaeoenvironment reconstruction are also provided. As such, an age of the sediments, and the palaeoenvironment are reconstructed using staphylinids, other fossil fauna, and taphonomical studied using the sediments. The depositional environment of the fossils is discussed, since a taphonomical analysis of the deposit was attempted. The preliminary results suggest that staphylinids inhabited the perimeter of the lake, and were trapped in a nearshore, shallow water oxidising environment. For some unknown reason, most of the plant material is preserved in presumably green, deeper water, unoxidising environment. This preliminary analysis needs expansion with a larger sample size. All three fossil insects belonging to the Steninae, Tachyporinae and Paederinae support the previous palaeoenvironmental reconstruction at Orapa as crater-lake situated in a moist, wellvegetated environment. Since all three subfamilies in this study contain numerous species and cannot be assigned to extant genera, it was not possible to draw more confident conclusions than this. The climate of the deposit in the Cretaceous has been reconstructed as being seasonal and interchanging between tropical and temperate extremes. Based on knowledge of other fossil finds, the staphylinids described here would be predicted to occur in the Cretaceous. The morphological conservatism of the described specimens, together with that of similarly-aged staphylinids, and many other insects, suggests a far more conservative rate of evolution than for vertebrates, which have undergone enormous change in the same period of time. These findings suggest a punctuated equilibrium pattern of evolution, as previously reported in McKay (1990) and Waters (1990).
A thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, University of the Witwatersrand, 2022
Keywords: Turonian; Steninae; Tachyporinae